Mechanical Properties Analysis of Flexible Memristors for Neuromorphic Computing - Zhenqian Zhu; Jiheng Shui; Tianyu Wang; Jialin Meng (Nano-Micro Letters)
Highlights This review systematically summarizes materials system, development history, device structure, stress simulation and applications of flexible memristors. This review highlights the critical influence of mechanical properties on flexible memristors, with particular emphasis on deformation parameters and finite element simulation. The applications of future memristors in neuromorphic computing are deeply discussed for next-generation wearable electronics